Dendritic Transport and Localization of Protein Kinase Mζ mRNA: IMPLICATIONS FOR MOLECULAR MEMORY CONSOLIDATION - Muslimov, Ilham Aliagaevich (2004)
Protein kinase Mζ (PKMζ) is an atypical protein kinase C isoform that has been implicated in the protein synthesis-dependent maintenance of long term potentiation and memory storage in the brain. Synapse-associated kinases are uniquely positioned to promote enduring consolidation of structural and functional modifications at the synapse, provided that kinase mRNA is available on site for local input-specific translation. We now report that the mRNA encoding PKMζ is rapidly transported and specifically localized to synaptodendritic neuronal domains. Transport of PKMζ mRNA is specified by two cis-acting dendritic targeting elements (Mζ DTEs). Mζ DTE1, located at the interface of the 5′-untranslated region and the open reading frame, directs somato-dendritic export of the mRNA. Mζ DTE2, in contrast, is located in the 3′-untranslated region and is required for delivery of the mRNA to distal dendritic segments. Colocalization with translational repressor BC1 RNA in hippocampal dendrites suggests that PKMζ mRNA may be subject to translational control in local domains. Dendritic localization of PKMζ mRNA provides a molecular basis for the functional integration of synaptic signal transduction and translational control pathways.